2023
DOI: 10.1021/acs.est.3c00823
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Exposure to Phthalates and Their Alternatives and Associated Female Reproductive Health: Body Burdens, Adverse Outcomes, and Underlying Mechanisms

Abstract: The global birth rate has recently shown a decreasing trend, and exposure to environmental pollutants has been identified as a potential factor affecting female reproductive health. Phthalates have been widely used as plasticizers in plastic containers, children's toys, and medical devices, and their ubiquitous presence and endocrine-disrupting potential have already raised particular concerns. Phthalate exposure has been linked to various adverse health outcomes, including reproductive diseases. Given that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 245 publications
0
9
0
Order By: Relevance
“…Notably, DINCH does not influence the activity of human nuclear receptors, including ERα, ERβ, AR, PPARα, and PPARγ, in HEK293 cell lines. 100 On the other hand, DINCH metabolites like M2NCH, MINCH, OH-MINCH, oxo-MINCH, and cx-MINCH have been shown to activate these receptors. The review also noted that limited studies hinder the complete understanding of the impact of emerging plasticizers on female reproductive health.…”
Section: An Overview Of Commonly Used Plasticizersmentioning
confidence: 99%
“…Notably, DINCH does not influence the activity of human nuclear receptors, including ERα, ERβ, AR, PPARα, and PPARγ, in HEK293 cell lines. 100 On the other hand, DINCH metabolites like M2NCH, MINCH, OH-MINCH, oxo-MINCH, and cx-MINCH have been shown to activate these receptors. The review also noted that limited studies hinder the complete understanding of the impact of emerging plasticizers on female reproductive health.…”
Section: An Overview Of Commonly Used Plasticizersmentioning
confidence: 99%
“…Pregnant women’s exposure to pollutants from various environmental matrices can have a negative impact on the fetus due to maternal–fetal transmission. In utero exposure to environmental pollutants and their health effects have received substantial attention. , Both extensive experimental animal studies as well as epidemiological findings have demonstrated that early-life environmental factors are associated with an increased risk of developing a variety of chronic illnesses in later life . Recent epidemiological and toxicological studies demonstrated that widely used plasticizers, including organic phosphate esters (OPEs) and phthalate acid esters (PAEs), are commonly present in utero and may exhibit strong embryonic and developmental toxicity early in life. However, most environmental epidemiologic studies have focused on monitoring parental exposure, and little is known about cumulative exposure in the intrauterine environment.…”
Section: Introductionmentioning
confidence: 99%
“…DBP is classified as an endocrine-disrupting chemical and potentially causes teratogenicity, mutagenicity, and carcinogenicity. Several studies have reviewed the association between DBP exposure and reproductive diseases, cardiovascular diseases, thyroid diseases, and other adverse effects that were confirmed by some cohort studies and animal model experiments. Previous works suggest that the potential mechanisms underlying toxicity of DBP may result from oxidative stress, inflammation, and epigenetic modifications, as well as further raising concerns at the subcellular level . Due to the hydrophobic nature of DBP with a high K ow (octanol–water partition coefficients: 3.74) and low vapor pressure, it is not unexpected that DBP tends to be attracted to lipid-rich organelles inside the cell such as mitochondria, the well-known predictive targets of chemical agents.…”
Section: Introductionmentioning
confidence: 99%